Uncharted phytochemical frontiers: a systematic review of novel bioactive compounds from underexplored aromatic plants for cancer therapy - Biswabhusan Dash; Himadri Tanaya Behera; N.G. Unnoottee; Swagat Mohanty; Divaker Shukla; Sudipta Jena; Asit Ray; Pratap Chandra Panda; Sanghamitra Nayak; Ambika Sahoo (Frontiers in Oncology, 2026)
Introduction Cancer continues to cause a high degree of morbidity and mortality worldwide, making it essential for new, safer, and more effective therapies to be developed. Aromatic plants provide researchers with diverse secondary metabolites that may have useful pharmacological effects. This systematic review examines several aromatic plants that were used medicinally in the past but have not been examined recently for their potential to produce new bioactive molecules with anticancer activity. Methods The protocol for this systematic review followed PRISMA 2020, and it aimed to assess the anticancer potential of bioactive compounds obtained from underexplored aromatic plants. Peer-reviewed articles reporting phytochemical isolation, structural characterization, biological evaluation, and mechanistic investigations were systematically retrieved and analyzed. Data on plant species, bioactive compounds, identification methods, cancer models, molecular targets, pharmacological activities, and translational evidence were extracted and synthesized. Results In this review, a variety of phytochemicals that exhibit strong anticancer effects were identified, including the following: monoterpenes, sesquiterpenes, diterpenoids, triterpenoids, flavonoids, steroid compounds and phenylpropanoids. In addition to the existing identified compounds, several new phytochemicals, named epunctanone, PCPT-1, aspiletrein A, paeoniflorigenone, 7,8-epoxynagilactone, compound 5o, and new derivatives of phorbol esters, demonstrated powerful cytotoxic activities in many cancer models. The mechanism by which these phytochemicals exert their anticancer effect has been studied, and several pathways identified including: induction of apoptosis, blockage of cell-cycle progression, modulation of oxidative stress, inhibition of angiogenesis and metastasis, as well as regulation of various critical kinase signaling pathways (e.g. PI3K/Akt/mTOR, MAPK, STAT3, EGFR, NF-κB). Conclusion Underexplored aromatic plants are a promising source of structurally diverse bioactive compounds with encouraging anticancer activity in preclinical studies. However, there is no convincing evidence from high-quality human clinical trials that essential oils or their constituents can directly treat or cure cancer. Further rigorous preclinical and clinical studies are needed to establish their safety and therapeutic efficacy. Challenges including phytochemical standardization, limited pharmacokinetic and toxicological data, insufficient in vitro validation, and lack of clinical studies continue to obstruct translational progress. Future research integrating advanced phytochemical characterization, molecular oncology, AI-assisted drug discovery, and nanotechnology-based delivery systems may facilitate the development of aromatic plant-derived anticancer therapeutics.